Calculation of Effective Coefficient of Thermal Expansion for Composite ‘Glass-Eucryptite’ Changing during Sintering; Applied Mechanics and Materials; Vol. 756 : Mechanical Engineering, Automation and Control Systems (MEACS2014) - Knyazeva A. G. Anna Georgievna (Modelling and Numerical Simulation, Algorithms and Mathematical Methods for Applied Problems, 2015)
Title screen